A rare case of giant mediastinal thymolipoma in an 18‐year man - Hourieh Soleimani; Behzad Aminzadeh; Ehsan Hassannejad; Asma Payandeh; Batul Oudi; Neda Karimabadi (Clinical Case Reports, 2024)
Key Clinical Message Thymolipoma is a rare benign thymic lesion that can manifest as a sizable anterior mediastinal mass. Considering their rarity and challenging preoperative diagnosis, it is crucial to consider these tumors when dealing with anterior mediastinal masses.